The Influence of Internal and External Forces in Adoption of Electronic Customer Relationship Management (eCRM) in Malaysian SMEs - Nasruddin, Nurul Hafizah; Abdul Khalid, Fararishah (Medwell Journals, 2017)
Information Technology (IT) plays a significant role in today’s business competition. A prominent role is that it helps a firm to manage relationships with customers effectively. Today’s online consumer has more complex needs and much higher expectations than ever before. Online business communities are fast emerging as new organizational tools for customer relationship management, marketing, brand management and for a multitude of other purposes such as building strong online trust and reciprocity. To support this capability, Customer Relationship Management (CRM) is evolving into electronic Customer Relationship Management (eCRM). Electronic Customer Relationship Management (eCRM) has become the latest paradigm in the world of Customer Relationship Management. The purpose of this paper is to examine the factors influencing the adoption of electronic Customer Relationship Management (eCRM) applications in Malaysian SMEs. The research contains 8 influencing factors covering four contexts: individual, technological, organizational, and environmental.